Chronic respiratory morbidity, musculoskeletal disorders and other self-reported illness among migrant brick kiln workers in rural South India (International Journal of Occupational Safety and Health, 2025)
Introduction: Brick kiln workers face a higher risk of respiratory issues like Chronic Bronchitis and Asthma due to exposure to fine particulate matter. This study aimed to assess the prevalence of these conditions, along with musculoskeletal discomfort and other self-reported morbidities, among workers in a rural health center’s field practice area.Methods: The This cross-sectional study included all men and women above 18 years of age (n=650) working in the 12 brick kilns in the study area.  Out of 650, 580 workers gave consent for study participation. A standardized and validated questionnaire (ICMR-INSEARCH) along with Peak Expiratory Flow Rate (PEFR) was used to assess the prevalence of respiratory morbidity. Other morbidities were assessed by history taking and clinical examination of the participants.Results: There were 580 workers, with a mean age of 36.47(SD 11.45) years. Of them, 66% were engaged in molding, 25% in carriage, and 6% in baking work. There were 15.2% smokers and 8.4% tobacco users.  Chronic bronchitis was present in 37 (6.4%) and Asthma in 12 (2.1%) workers. Higher age (>50 years) was associated with chronic bronchitis. (p